The Legal Solutions in the Field of Financial and Budgetary Discipline in France in the Light of the Code of Finance Jurisdiction - Małgorzata Cilak (Prawo Budżetowe Państwa i Samorządu)
The purpose of this article is to present French institutional and law solutions in the field of public finance discipline. The article describes legal position and functioning of Court of Budgetary and Finance Discipline in France. The jurisdiction of Court covers the cases of serious breach of public finance law. The Court is one of the elements of the system of jurisdiction in financial matters, that constitute a specialized type of administrative jurisdiction. The law that regulate the legal position and functioning of the Court, as well as the actes which are breaches of public finance discipline, and the sanctions for them, is the Code of finance jurisdiction (Code des juridictions financières).